2010
DOI: 10.1590/s0100-67622010000600011
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do impacto do fogo no estrato de regeneração em um trecho de Floresta Estacional Semidecidual em Viçosa, MG

Abstract: -This study was carried out in a fragment of a Seasonal Semideciduous Forest, which belongs to the Universidade Federal de Viçosa, Minas Gerais,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
0
5
0
7
Order By: Relevance
“…The seasonal forest, unlike Cerradão and "Cerrado stricto sensu", does not present direct adaptations to resist the passage of fire, such as coarse bark and seasonal loss of foliage. Thus, once burned, the trees die directly or weaken and can lead to death in the long term (one year to five years) (FELFILI, 2003;CAMARGOS et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The seasonal forest, unlike Cerradão and "Cerrado stricto sensu", does not present direct adaptations to resist the passage of fire, such as coarse bark and seasonal loss of foliage. Thus, once burned, the trees die directly or weaken and can lead to death in the long term (one year to five years) (FELFILI, 2003;CAMARGOS et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…A Reserva da Biologia possui 75 ha, que estão protegidos de desmatamento há 90 anos (Ferreira-Junior et al, 2007). Essa reserva tem as funções de conservar a biodiversidade da Floresta Estacional Semidecidual e permitir a execução de pesquisas em comunidades florestais (Ferreira-Junior et al, 2007;Camargos et al, 2010). Na área de borda desse fragmento, segundo a Divisão de Parques e Jardins da UFV, há 40 anos foi realizado o plantio experimental de Araucaria angustifolia, que desde então foi protegido e mantido sem ações de manejo.…”
Section: Methodsunclassified
“…Also Camargos et al (2010), in a study on the impact of fire on the regeneration stratum in a semideciduous seasonal forest stretch in Viçosa (MG), observed that there was a significant reduction in diversity before and after a fire, concluding that frequent fires on a major scale can severely alter the composition and structure of the forest fragments that favor species with a capacity for regrowth, to the detriment of the others.…”
Section: Introductionmentioning
confidence: 99%